AN IOT BASED SMART E-FUEL STATION USING ESP-32 - Dr. Y. Mallikarjuna Rao; Surendra, Beegala; Konda Govardhan; A. Madhava Reddy; B. Mallikarjuna; P. Sayyed Basha (RADJA PUBLIKA, 2023)
IoT and Cloud computing is becoming more in demand now days due to advancement in its technology. Most of the fuel stations these days are operated manually which are time consuming and require more manpower. It is very difficult and costly to provide excellent facility to the consumers in a fuel station present in a distant area. All these problems can be solved by the use of the proposed project. This paper presents the design and implementation of a smart e-fuel station using IoT technology in which the system is capable of deducting the amount of petrol dispensed from a user-based card using RFID technology and measure the level of fuel in the station and upload it to the cloud server. This cloud server is only accessible to the admin. If the fuel level is low then the main station will provide the fuel to that station. Everything is getting automated in today’s world. Existing system: In previous we have seen in fuel station to fill the fuel we need human help needed for filling the fuel and there is no proper protection in fuel stations like fire sensor, smoke sensor etc. this lead to damage and also fire accidents. Proposed system: The system proposed describes the creation and management of a smart fuel. An interactive, digital system is designed to improve user interface. It uses a data procurement system based on the microcontroller that uses AC to bring control data from analog to digital format. Tough the in-vehicle information systems are spread throughout a practical vehicle’s body, a communication module is adopted which supports the incorporation of a controlled fuel dispensing system for vehicles through an ESP32 microcontroller-controlled device. In this work the Automatic vehicle identification (AVI) system is adopted and further the customer will scan his RFID/Wi-Fi card with all the details installed in it.